Adult Density of Culex quinquefasciatus Say, Filarial Vector in Thapa Gaun, Jhaukhel and Lama Tole, Nagarkot VDC, Bhaktapur District - Byanju, Reena; Gautam, Ishan; Aryal, Manchita; KC, Aradhana; Shrestha, Hum Narayan; Dhimal, Meghnath (Nepal Journal of Science and Technology, 2013)
A six month long entomological study on the adult density of Culex quinquefasciatus Say, the principal vector of filariasis was conducted during April to September 2011 at Thapa Gaun, Jhaukhel and Lama Tole, Nagarkot VDCs of Bhaktapur district. The study resulted 916 (882 female and 34 male) C. quinquefasciatus out of the total collected mosquitoes (3040). The population density was found to be highest in Thapa Gaun (26.09) while indoor density was relatively higher than the outdoor density for both the sites which were significantly related. Monthwise densities were insignificantly related with July showing the highest density while the density in human residence and cattle shed were insignificantly related for Jhaukhel site and was significantly related with Nagarkot site. Morning and evening population densities were significantly related for both sites while no significant relationship was observed between the density of the vector and temperature and variation in temperature and humidity in the study area. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 185-194 DOI: http://dx.doi.org/10.3126/njst.v14i1.8939